Major changes in grapevine wood microbiota are associated with the onset of esca, a devastating trunk disease. (6th September 2020) - Bruez, Emilie; Vallance, Jessica; Gautier, Angélique; Laval, Valérie; Compant, Stéphane; Maurer, Wolfgang; Sessitsch, Angela; Lebrun, Marc‐Henri; Rey, Patrice
Summary: Esca, a major grapevine trunk disease in old grapevines, is associated with the colonization of woody tissues by a broad range of plant pathogenic fungi. To identify which fungal and bacterial species are involved in the onset of this disease, we analysed the microbiota from woody tissues of young (10‐year‐old) grapevines at an early stage of esca. Using meta‐barcoding, 515 fungal and 403 bacterial operational taxonomic units (OTUs) were identified in woody tissues. In situ hybridization showed that these fungi and bacteria co‐inhabited in grapevine woody tissues. In non‐necrotic woody tissues, fungal and bacterial microbiota varied according to organs and seasons but not diseased plant status. Phaeomoniella chlamydospora, involved in the Grapevine trunk disease, was the most abundant species in non‐necrotic tissues from healthy plants, suggesting a possible non‐pathogenic endophytic behaviour. Most diseased plants (70%) displayed cordons, with their central white‐rot necrosis colonized essentially by two plant pathogenic fungi ( Fomitiporia mediterranea : 60%–90% and P. chlamydospora : 5%–15%) and by a few bacterial taxa ( Sphingomonas spp. and Mycobacterium spp.). The occurrence of a specific association of fungal and bacterial species in cordons from young grapevines expressing esca‐foliar symptoms strongly suggests that that microbiota is involved in the onset of this complex disease.